Factors and Counseling Techniques: Self-Management as an Approach to Addressing Online Shopping Consumption Behavior - Umairah, Siti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research was conducted with the aim of observing and providing an overview of consumer behavior factors in online shopping. The method used in this research is literature study. The literature study itself is solely carried out by reviewing and analyzing the topic or theme being discussed. Based on the research that has been carried out, the results obtained are: consumer behavior is an act of using or spending a product that is incomplete, buying without any intention of giving, buying a product just because many people use the product. e-commerce is a development in an electronic trading system. where e-commerce is part of a lifestyle that carries out buying and selling transactions via online media in various places and at any time. Factors that can influence someone to carry out consumer behavior or hedonism can be internal or external. External factors consist of marketing or product promotion efforts, advertising, prices and discounts as well as the influencing socio-cultural environment consisting of the family as a source of information, non-commercial sources, social class, subculture and culture. Meanwhile, internal factors come from consumer psychology which consists of motivation, perception, learning, peers, personality and attitude.